The challenge of integrated water resource management for improved rural livelihoods: Managing risk, mitigating drought and improving water productivity in the water scarce Limpopo Basin - Ncube, B.; Manzungu, Emmanuel; Love, David; Magombeyi, Manuel Simba; Gumbo, B.; Lupankwa, K. (CGIAR Challenge Program on Water and Food, 2010)
The Challenge of Integrated Water Resource Management for Improved Rural Livelihoods: Managing Risk, Mitigating Drought and Improving Water Productivity in the Water Scarce Limpopo Basin: Integrated Water Resources Management (IWRM) is a systems approach to water management, based on the principle of managing the full water cycle. It is required, not only to balance water for food and nature, but also to unlock paths to sustainable development. A global hotspot area in terms of water for food and improved livelihoods is in the poverty stricken rural areas of water scarce semi-arid tropics, such as in the Limpopo basin. The improvement in resilience that the IWRM approach can impart to rural livelihood systems has been shown by a series of case studies in the Limpopo Basin.